Impact of internal branding and corporate culture on employee brand support and the role of corporate identity as mediator - Razak, Muhammad Nur Fitri (2022)
Corporate identity has played a vital role in the halal industry to create a strong foundation for its reputation in the long run. This paper used two modeling analyses for two different data. The first analysis aimed to predict the relationship between internal brand (antecedent) and corporate culture (antecedent), and employee brand support (consequence), mediated by corporate identity management (CIM) using partial-least squares-structural equation modeling (PLS-SEM). A total of 206 employees from Malaysia’s halal food SMEs took part in the survey. The second analysis identified topic proportions patterns using the topic modeling approach on halal brand identity. Machine learning approach of topic modeling was applied for this analysis. Metadata of 1,091 articles were mined from the Scopus database on halal studies across all social sciences fields. The result of the first analysis revealed that there was a partial relationship between internal brand (antecedent) and employee brand support (consequence) mediated by CIM. The second analysis supported these findings by pointing out a weak topic proportion on the halal brand identity discussion globally. Interestingly, the result also found the halal brand identity discussion involving the halal food industry is almost non-existed in Malaysia’s halal food SMEs. The contributions of this paper were apparent in three major areas which are methodology, theoretical and future suggestions. The utilization of two different model analyses was able to confirm the consistency of the discussions of major findings in the literature review, and proposed possible studies for future researchers.